The Dilemma of Unrelenting Workload Amidst Covid-19 Pandemic: An Agenda for University Female Academics - Obianuju E. Okeke-Uzodike (University Babes-Bolyai, 2021)
The dynamic changes in the South African higher education environment system have seen academics immersed in increasing workloads to keep up with the university mandate. The outbreak of the Covid-19 pandemic has raised significant challenges for the higher education community and intensified complications related to workload and in particular for female academics. The understanding of the management of workload is pertinent, and therefore the article examines the components of workload and implications of the Covid-19 pandemic for female academics. A descriptive research design and a quantitative research approach were adopted, and data was collected from 54 female academics in an unidentified university in South Africa. The data was analyzed using the Statistical Packages for Social Sciences (SPSS) version 26 and presented using a descriptive and inferential format. Also, the study also adopted a systematic review of literature leveraging reputable sources. The findings revealed that (i) time allocation to academic activities of teaching and learning, research, postgraduate supervision, administration matters, community service, and academic citizenship remains a challenge facing universities, and (ii) Covid-19 imposed remote working arrangements resulting in increased workloads, leading to reduced research productivity and inability to achieve work-life balance for the female academics. The results of the study highlight the need for institutional review and policy development on the academic workload management system to ensure work-life balance for the female academics and output maximization for the university, especially during a pandemic.